FACTORS INFLUENCING THE STUDENTS SWITCHING BEHAVIOUR IN THE PURCHASE OF SMART PHONE - Vasigar, V.; Velmurugan, Dr. V. (IJRDO - Journal of Business Management, 2018)
Switching behaviour is referred to the times when consumer chooses a competing choice rather than the previously purchased choice on the next purchase occasion. This research made an attempt to identity the factors influencing the students switch over the smart phone in the Pondicherry State. Smart phone product feature, pricing, promotion peer group, brand and internet factors are considered as the influencing factors for switch over behaviour of students in the purchase of smart phone. Descriptive research is applied. For collecting the primary data, questionnaire method survey was employed. By using convenience sampling technique, 152 students were surveyed. Correlation and regression analysis were applied to know the influencing factor. It is found that brand, promotion and pricing factors are influenced the students to switch over the smart phone.